Pyrolysis-GC/MS Analysis of Fast Growing Wood Macaranga Species - R.R. Dirgarini J.N. Subagyono; Ying Qi; Alan L. Chaffee; Rudianto Amirta; Marc Marshall (Universitas Pendidikan Indonesia, 2021)
Py-GC/MS analysis of six different species of fast growing Macaranga wood has been studied. Flash pyrolysis was conducted at different temperatures (250-850 oC) under a flow of helium followed by GC/MS analysis of the products. The total pyrolysis yields of the six different species of Macaranga were mostly between 40 and 90% within the range of pyrolysis temperature applied. Pyrolysis of the woody biomass produced compounds which are mostly derived from thermal degradation or volatilization of lignin and cellulose/hemicellulose, the original major constituents of the biomass. The Py-GC/MS technique indicated that M. gigantea was the most potential species for biofuel production and the optimum pyrolysis temperature to produce high yields of bio-oil was 450 oC.